2020
DOI: 10.26434/chemrxiv.12941606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interaction Analyses on SARS-CoV-2 Spike Protein Based on Large-Scale Correlated Fragment Molecular Orbital Calculations

Abstract: At the stage of SARS-CoV-2 infection to human cell, the spike protein consisting of three chains, A, B and C, with a total of 3.3 thousand residues plays the key role, and thus its nature have attracted considerable interests. Here, we report interaction analyses on the spike protein of both closed (PDB-ID: 6VXX) and open (6VYB) structures, based on large-scale fragment molecular orbital (FMO) calculations at the level of up to the fourth-order Møller-Plesset perturbation with singles, doubles and quadruples (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…[40][41][42] In recent years, the FMO method has been widely used as a drug discovery tool. 35,[43][44][45][46][47][48][49][50][51][52] Recent studies have also provided detailed information on the underlying antigen-antibody or ligandbinding characteristics of several drug-targeted proteins, main protease [53][54][55] , RNA-dependent RNA polymerase 56 , S-protein 17,19 , in COVID-19. To date, the FMO method has been successfully used for identifying key amino acid residues and sugar chains for PPI, such as molecular recognition for an influenza hemagglutinin of a fragment antigen-binding (Fab) antibody [57][58][59][60][61][62][63][64][65][66][67] and a measles hemagglutinin of a signaling lymphocytic activation molecule 68,69 .…”
mentioning
confidence: 99%
“…[40][41][42] In recent years, the FMO method has been widely used as a drug discovery tool. 35,[43][44][45][46][47][48][49][50][51][52] Recent studies have also provided detailed information on the underlying antigen-antibody or ligandbinding characteristics of several drug-targeted proteins, main protease [53][54][55] , RNA-dependent RNA polymerase 56 , S-protein 17,19 , in COVID-19. To date, the FMO method has been successfully used for identifying key amino acid residues and sugar chains for PPI, such as molecular recognition for an influenza hemagglutinin of a fragment antigen-binding (Fab) antibody [57][58][59][60][61][62][63][64][65][66][67] and a measles hemagglutinin of a signaling lymphocytic activation molecule 68,69 .…”
mentioning
confidence: 99%
“…Interaction analyses between S-protein and hACE2 or B38 Fab antibodies using the FMO method have been reported. 47 49 This study focused on 12 antibodies/peptides (LCB1, 27 LCB3, 27 C105, 23 COVA2-04, 21 BD-604, 26 CB6, 17 B38, 17 BD-629, 26 C102, 22 CC12.3, 19 CC12.1, 19 and CV30 17 ) and analyzed the interactions between these antibodies/peptides and the RBD using the FMO method. To obtain more useful information for rational antibody design, we further estimated the importance of amino acid residues and regions in the RBD for antibody/peptide binding.…”
mentioning
confidence: 99%
“…The results of in silico mutational screening that are based on knowledge-based mean force potentials are consistent with more detailed and laborious quantum chemical-based fragment molecular orbital (FMO) evaluation of the SARS-CoV-2 S-protein binding with the B38 Fab antibody. 97,98 By analyzing FMO-based interaction energies 98 , a range of residues critical for molecular recognition with B38 Fab antibody was identified that also included R403, Q409, K458, G476, N501, G502, V503, G504, and Y505 sites.…”
mentioning
confidence: 99%